1983
DOI: 10.1111/j.1365-2621.1983.tb10739.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rate and Length of Cookery upon Product Attributes of Pre‐ and Post‐Rigor Beef

Abstract: Paired sides of 15 steer carcasses were used to determine the effects of low temperature, long duration cooking upon muscle (semimembranosus, SM; semitendinosus, ST) shortening, cooking and tenderness attributes of beef roasts that were removed 1 hr (hot-boned, HB) and 48 hr postmortem (cold-boned, CB). The cooking treatments were: (1) 1st hr at 47'C then raised 5.6'C/hr through the 5th hr (69°C); (2) 1st hr at 52°C then raised 5.6"C/hr through the 4th hr (69'C); and (3) 1st hr at 58'C then raised 5.6"C/hr thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Henning et al (1973) cooked samples from three bovine muscles (biceps femoris, semitendinosus, and semimembranosus) at 3 postmortem times (1 hr, 48 hr, and 5 days) and found tenderness increased from the first sampling time to the third. Ray et al (1983) cooked beef semimembranosus and semitendinosus roasts and Loucks et al (1984) cooked beef semimembranosus roasts at 1 hr and 48 hr postmortem and found that shear values and sensory panel ratings showed that prerigor cooked roasts were less tender than postrigor cooked roasts. Shin et al (1993) cooked pork and beef roasts from triceps brachii in a conventional oven at 150, 200, or 250°C and reported that prerigor cooked roasts were less tender than postrigor cooked roasts.…”
Section: Introductionmentioning
confidence: 99%
“…Henning et al (1973) cooked samples from three bovine muscles (biceps femoris, semitendinosus, and semimembranosus) at 3 postmortem times (1 hr, 48 hr, and 5 days) and found tenderness increased from the first sampling time to the third. Ray et al (1983) cooked beef semimembranosus and semitendinosus roasts and Loucks et al (1984) cooked beef semimembranosus roasts at 1 hr and 48 hr postmortem and found that shear values and sensory panel ratings showed that prerigor cooked roasts were less tender than postrigor cooked roasts. Shin et al (1993) cooked pork and beef roasts from triceps brachii in a conventional oven at 150, 200, or 250°C and reported that prerigor cooked roasts were less tender than postrigor cooked roasts.…”
Section: Introductionmentioning
confidence: 99%